Assessment of impact of adoption of improved cassava varieties on yields in Ghana: An endogenous switching approach - Patricia Pinamang Acheampong; Monica Addison; Camillus Abawiera Wongnaa (Cogent Economics & Finance, 2022)
The paper assesses the potential impact of the adoption of improved cassava varieties on yields of smallholder farmers. Agricultural intensification is associated with increasing yields per hectare through the use of improved varieties. Studies have established the relationship between adoption and yield, yet this relationship is understudied in the cross-national literature. Using cross-sectional data collected from a randomly selected sample of 1,176 farmers dispersed across Ghana and employing an endogenous switching regression model, the causal impact of improved variety adoption was estimated. Our results revealed that adoption decisions were conditioned by age, extension access, extension visits, awareness and farm size. Also, adoption had a significant positive impact on cassava yields. Adopters had 18 t/ha increases in yields and non-adopters should they have adopted had increases of 10 t/ha. Strategies to resource research extension linkage system to promote and create awareness about the existing improved cassava varieties for increased adoption are recommended.
Keywords: 330; Adoption; awareness; dissemination; smallholder farmer; switching regression